2020 ACA Election: Candidates and Voting Instructions. - Gondles Jr., James A. (Corrections Today)
The article informs that candidates selected by American Correctional Association's Nominating Committee, were chosen for president-elect, vice president and treasurer positions, along with nominees to the Board of Governors. Topics include Doug Dretke has served focused on training and professional development needs of correctional professionals across the broad spectrum of corrections; and Denise M. Robinson has worked as national and international leaders to create prison and jail policies.